AN EXPOSITION OF ISLAMIC SOLUTIONS TO CHALLENGES FACING MUSLIMS IN TARABA STATE (1991-2021) - Bello Ali (Profetika: Jurnal Studi Islam, 2023)
Taraba State is heterogeneous consisting of several ethnic groups with divergent historical origins, cultural activities, and religious belief systems. The different communities actively participate in collective endeavours such as agriculture and developing essential infrastructure including culverts, houses, and schools. However, after the creation of the State, the atmosphere of harmonious coexistence started to shift towards hostility. The study aimed at the comprehensive exposition of Islamic solutions to challenges facing Muslims in Taraba. This study's primary and secondary data were derived principally through structured interviews, participatory observation, and analysis of documentary sources. The study made some significant findings, including a cordial relationship between Muslims and non-Muslims. The challenges identified include internal divisions, limited political influence, self-centeredness and animosity within the Muslim community, flawed approaches of some scholars, and a decline in moral values among Muslims. Ethnic identity, indigeneity, and minority issues also contribute to the challenges. To address these challenges, the study recommends efficient Da’wah activities, the establishment of unified leadership, the revitalization of moral teachings, and the implementation of Islamic endowment (Waqf) practices. The effective implementation of these recommendations can help mitigate the challenges faced by Muslims in Taraba State.